Preclinical pharmacokinetics and pharmacodynamics of DCLL9718A: An antibody-drug conjugate for the treatment of acute myeloid leukemia. Issue 8 (17th November 2018) - Leipold, Douglas D.; Figueroa, Isabel; Masih, Shabkhaiz; Latifi, Brandon; Yip, Victor; Shen, Ben-Quan; Dere, Randall C.; Carrasco-Triguero, Montserrat; Lee, M. Violet; Saad, Ola M.; Liu, Luna; He, Jintang; et al.
ABSTRACT: Few treatment options are available for acute myeloid leukemia (AML) patients. DCLL9718A is an antibody-drug conjugate that targets C-type lectin-like molecule-1 (CLL-1). This receptor is prevalent on monocytes, neutrophils, and AML blast cells, and unlike CD33, is not expressed on hematopoietic stem cells, thus providing possible hematopoietic recovery. DCLL9718A comprises an anti-CLL-1 IgG1 antibody (MCLL0517A) linked to a pyrrolobenzodiazepine (PBD) dimer payload, via a cleavable disulfide-labile linker. Here, we characterize the in vitro and in vivo stability, the pharmacokinetics (PK) and pharmacodynamics (PD) of DCLL9718A and MCLL0517A in rodents and cynomolgus monkeys. Three key PK analytes were measured in these studies: total antibody, antibody-conjugated PBD dimer and unconjugated PBD dimer. In vitro, DCLL9718A, was stable with most (> 80%) of the PBD dimer payload remaining conjugated to the antibody over 96 hours. This was recapitulated in vivo with antibody-conjugated PBD dimer clearance estimates similar to DCLL9718A total antibody clearance. Both DCLL9718A and MCLL0517A showed linear PK in the non-binding rodent species, and non-linear PK in cynomolgus monkeys, a binding species. The PK data indicated minimal impact of conjugation on the disposition of DCLL9718A total antibody. Finally, in cynomolgus monkey, MCLL0517A showed target engagement at all doses tested (0.5 and 20 mg/kg) as measured by receptor occupancy, and DCLL9718A (at doses of 0.05, 0.1 and 0.2 mg/kg) showed strong PD activity as evidenced by notable reduction in monocytes and neutrophils.